Effect of Oral Lipid Matrix Supplement on Fat Absorption in Cystic Fibrosis: A Randomized Placebo-Controlled Trial. Issue 6 (December 2016) - Stallings, Virginia A.; Schall, Joan I.; Maqbool, Asim; Mascarenhas, Maria R.; Alshaikh, Belal N.; Dougherty, Kelly A.; Hommel, Kevin; Ryan, Jamie; Elci, Okan U.; Shaw, Walter A.
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: Pancreatic enzyme therapy does not normalize dietary fat absorption in patients with cystic fibrosis and pancreatic insufficiency. Efficacy of LYM-X-SORB (LXS), an easily absorbable lipid matrix that enhances fat absorption, was evaluated in a 12-month randomized, double-blinded, placebo-controlled trial with plasma fatty acids (FA) and coefficient of fat absorption (CFA) outcomes. A total of 110 subjects (age 10.4 ± 3.0 years) were randomized. Total FA increased with LXS at 3 and 12 months (+1.58, +1.14 mmol/L) and not with placebo ( P  = 0.046). With LXS, linoleic acid (LA) increased at 3 and 12 months (+298, +175 nmol/mL, P   ≤  0.046), with a 6% increase in CFA ( P   <  0.01). LA increase was significant in LXS versus placebo (445 vs 42 nmol/mL, P   =  0.038). Increased FA and LA predicted increased body mass index Z scores. In summary, the LXS treatment improved dietary fat absorption compared with placebo as indicated by plasma FA and LA and was associated with better growth status.